Culinary Business Mentoring for Housewives: Turning Passion into Profit - Iqbal, Khurshed (Edujavare Publishing, 2024)
This community service initiative aimed to empower homemakers by providing culinary business mentoring, helping them transform their passion for cooking into profitable home-based enterprises. With the increasing need for economic independence and skill development among homemakers, this program sought to address gaps in entrepreneurial knowledge, digital marketing, and business strategies. Using a Participatory Rural Appraisal (PRA) approach, the mentoring model included hands-on workshops, one-on-one guidance, and peer collaboration over four months. The results showed significant improvements in participants' business knowledge, digital literacy, and income, with many reporting a 40-60% increase in monthly earnings. Participants also experienced a shift in mindset, viewing themselves as entrepreneurs rather than just homemakers. While the program was successful, limitations such as time constraints and access to digital tools were noted. Future programs should incorporate flexible learning schedules and further digital infrastructure support. This initiative contributes to the growing recognition of homemakers as key economic actors, offering a scalable model for empowering women in local communities.